ANALISIS FAKTOR RISIKO CARPAL TUNNEL SYNDROME PADA PEGAWAI DI UNIVERSITAS PRIMA INDONESIA - Ariella N.M Sinuraya; Johannes Bastira Ginting; Pahala MJ Simangunsong (LPPM STIKes Mitra Adiguna, 2026)
Carpal Tunnel Syndrome (CTS) is a neuropathy caused by compression of the median nerve within the carpal tunnel; it is frequently experienced by workers engaged in repetitive activities, including computer users. This condition is classified as a Musculoskeletal Disorder (MSD) that can reduce workers' productivity and quality of life. This study aimed to analyze the relationship between risk factors—specifically age, gender, BMI, work duration, and work posture—and the incidence of CTS among UNPRI employees. The theoretical framework was based on concepts of occupational ergonomics, individual and occupational risk factors, and CDC BMI classifications. A cross-sectional analytical design was employed, involving 55 respondents selected via purposive sampling. Primary data were collected using validated questionnaires, BMI measurements, and work posture assessments, while secondary data were obtained from institutional records. Data analysis was performed using the Chi-Square test via SPSS. The results showed a CTS prevalence of 9.1%. Statistical tests indicated no significant association between CTS complaints and age (p=0.643), gender (p=0.327), BMI (p=0.526), work duration (p=1.000), or work posture (p=0.622). It is concluded that none of the five studied risk factors showed a significant association with the incidence of CTS; this may be attributed to the predominance of a younger age group and other factors not examined in this study.